The changes of wheat seedlings in drought condition by exogenous coronatine (COR) - Yanjing Wang; Zhihong Wang; Shuai Wang; Jianmin Li; Xiangdong Li; Hecang Zang; Baoting Fang (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2020)
Under drought and normal conditions, exogenous coronatine (COR), by the way of spraying, could induce the resistance of wheats (JiMai22 and LiangXing99). As a kind analogue of JA-Ile and compared to water-spraying, COR-spraying could improve water metabolism, photosynthesis, antioxidant enzymes activity and reduce the MDA and super anion contents. Moreover, though the way of JA acted with other hormones, especially the ABA, to regulate the plant growth, and then improve the drought resistance.